Design Enterprise Architecture Pada Tahapan Pembelian Rumah di Perusahaan Property - Prashanti Dewi, Made Dhanita Listra (Universitas Multi Data Palembang, 2024)
The property industry in Indonesia has become a dynamic force driven by strong economic growth, continuous urbanization, and rapid expansion of the middle class. The demand for residential, commercial, and industrial properties continues to soar, fueled by the aspirations of the younger generation and the government's commitment to extensive infrastructure development, providing housing for the population as a primary need. Facing the ongoing growth dynamics of the property industry and technological advancements, property businesses need to undergo digital transformation to maximize and streamline their business processes when buying a house to remain competitive in the property market. To achieve digital transformation, comprehensive planning is required, including the creation of Enterprise Architecture to provide a holistic view of the structure, business processes, information technology, and other resources within a company. Subsequently, the architecture diagram is detailed further using the Archimate application, enabling a clear delineation of interactions between business processes, data, servers, applications, and business actors. As a result, an application architecture framework is established for a property company.